Trainers’ Qualifications in Competence Based Education and Training Im plementation and Acquisition of Employable Skills Among Visually Impai red Learners in TVET Institutions in Kenya - Nduku Mutua, Priscillah; Mulwa, David; Kimiti, Richard (2019)
The purpose of this study was to examine the extent to which trainers’ qualifications in CBET implementation influence the acquisition of em ployable skills among visually impaired learners in TVET institutions in Kenya. The study applied a mixed methods research design. The study targeted 2 principals, 20 heads of departments, 70 trainers, 150 visu ally impaired learners and graduates of Machakos Technical Institute f or the Blind and Sikri Technical Training Institute for Deaf-Blind, 2 Ministry of Education officials in charge of TVET, Curriculum Developm ent Accreditation and Certification Council officials, 3 Ministry of L abour officials, 10 members of civil society groups and 5 managers of industries. A census of the principals and trainers was taken while pu rposive sampling was used to sample the rest of the respondents. Prima ry data was collected using questionnaires, interview schedules, focus ed group discussion guide and observation checklists. Quantitative dat a was analyzed using descriptive and inferential statistics while qual itative data was analyzed using content analysis. The study establishe d a shortage of trainers in most departments within the institutes att ributable to continuous increase in learners with special needs and mu ltiple disabilities and the requirement for one trainer per learner at a given time for learners with visual impairments. It was also establ ished that quite a large number of trainers in the TVET institutions w ere not adequately equipped to implement the CBET approach with a part icular focus on the visually impaired learners (VILs). The study furth er noted that the acquisition of employable skills among VILs was posi tively and significantly influenced by trainers’ qualifications in CBE T implementation. The study concluded that trainers’ qualifications ha d considerable impact of level of the acquisition of employable skills among VILs. Keywords: Competence based education and training, employ able skills, trainers’ qualifications, visually impaired learners. DOI : 10.7176/JEP/10-29-02 Publication date :October 31 st 2019